2004
DOI: 10.1021/jp0462862
|View full text |Cite
|
Sign up to set email alerts
|

Deliquescence and Crystallization of Ammonium Sulfate Particles Internally Mixed with Water-Soluble Organic Compounds

Abstract: The deliquescence and crystallization of ammonium sulfate particles internally mixed with water-soluble organic material have been studied, restricted to an organic mass fraction of less than 0.6. The organic species used were malonic acid, glycerol, levoglucosan (1,6-anhydro-β-d-glucopyranose), and Suwannee River fulvic acid. Our deliquescence results for systems with malonic acid and fulvic acid are in agreement with existing literature values. Glycerol deliquescence results are slightly lower than previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
139
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 56 publications
18
139
1
Order By: Relevance
“…However, no complete crystallization was observed in particle 2 down to 1% RH. The observations generally agreed with the results by Braban et al (2004) and Parsons et al (2004) who detected no crystallization of submicron particles and observed CRHs between 0 and 20% RH. It is clear that MA could significantly suppress or even inhibit the crystallization of AS in this system.…”
Section: Partial Phase Transitions Of As-organic Mixedsupporting
confidence: 92%
See 1 more Smart Citation
“…However, no complete crystallization was observed in particle 2 down to 1% RH. The observations generally agreed with the results by Braban et al (2004) and Parsons et al (2004) who detected no crystallization of submicron particles and observed CRHs between 0 and 20% RH. It is clear that MA could significantly suppress or even inhibit the crystallization of AS in this system.…”
Section: Partial Phase Transitions Of As-organic Mixedsupporting
confidence: 92%
“…The further increase in fwhh at 74% suggests that the AS fraction completely deliquesced at this RH. The complete DRH found in this study also agreed well with the 73.4% RH reported by Parsons et al (2004).…”
Section: Partial Phase Transitions Of As-organic Mixedsupporting
confidence: 91%
“…Meanwhile, the crystallization of AS is also influenced due to the presence of OA. A similar phenomenon was also observed for malonic acid / AS mixtures with minor organic content (Braban and Abbatt, 2004;Parsons et al, 2004). Braban and Abbatt (2004) found that the ERH of malonic acid / AS mixed particles was considerably decreased compared to that of pure AS for mass fractions of malonic acid less than 0.3.…”
Section: Hygroscopic Growth Of Pure and Mixed Componentssupporting
confidence: 72%
“…Using this simplified approach, it was determined that atmospheric aerosol in the Po valley in Italy exhibits a seasonal profile, with mono-and dicarboxylic acids dominating in the summer and polycarboxylic acids in spring, winter and autumn (Decesari et al, 2001). NMR profiles of the atmospheric aerosol were found to be similar to those obtained from terrestrial fulvic acids, for example Suwannee River fulvic acid (SRFA, Cappiello et al, 2003), which has been used as a surrogate for ambient aerosol in studies of physico-chemical properties (Parsons et al, 2004;Topping et al, 2005b;Dinar et al, 2006b). This technique has been used in numerous studies, including source identification and a recent improvement involves the derivatization of the carboxylic group with diazomethane to allow a direct determination of carboxylic acids in WSOC .…”
Section: Off-line High Complexity Soa Measurementsmentioning
confidence: 98%